Antifungal activity and chemical composition of the essential oil from the aerial parts of two new Teucrium capitatum L. chemotypes from Sardinia Island, Italy. Issue 24 (17th December 2021) - Maccioni, Alfredo; Falconieri, Danilo; Porcedda, Silvia; Piras, Alessandra; Gonçalves, Maria José; Alves-Silva, Jorge M.; Salgueiro, Ligia; Maxia, Andrea
Abstract: The chemical composition of two populations of Teucrium capitatum L. one from the coastline and the other one from the mountainous area of Sardinia (Italy) was assessed. Two chemotypes were identified: limonene/α-pinene/(E)-nerolidol chemotype predominant in the coastline, and limonene/α-pinene/α-trans-bergamotene/humulene epoxide II chemotype common in plants growing in the mountainous area. In addition, our results showed that the sample growing in the coastline had a more promising antifungal activity. Furthermore, this sample was highly effective in inhibiting C. albicans germ tube formation, at doses well below its MIC. Overall, this study shows that the edaphoclimatic characteristics play an important role on the essential oil composition and biological activity of Teucrium capitatum L. Abstract : UF0001